2004
DOI: 10.1002/icd.349
|View full text |Cite
|
Sign up to set email alerts
|

Imaginary companions: An evaluation of parents as reporters

Abstract: Parents are often solicited as reporters on their children's imaginary companions (ICs), but the correspondence between their reports and children's descriptions of pretend friends has received little attention. Sixty 4-year-old children and their parents provided descriptions of the children's interest in fantasy play, and 40 of these pairs also reported on children's ICs (20 on invisible friends and 20 on personified objects such as dolls). Results indicated that reports from parents of children with ICs mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 20 publications
1
24
0
1
Order By: Relevance
“…Consistent with what is found in the research literature, many mothers report that such speech use is more common when parents are not present, however, parents also correctly reported that the effect of parental presence on children's private speech depends on the situation (Behrend et al, 1992;Lee, 1999;Winsler, 1998, Winsler & Diaz, 1995. Thus, similar to what has been found concerning the usefulness of maternal reports for studying other, rather specific and curious child behaviours, such as the presence of imaginary companions and personified objects (Gleason, 2004), it would appear that maternal reports may provide useful information about children's private speech as well. Parents were also practically uniformly positive in their attitudes about private speech use in their children.…”
Section: Discussionsupporting
confidence: 57%
“…Consistent with what is found in the research literature, many mothers report that such speech use is more common when parents are not present, however, parents also correctly reported that the effect of parental presence on children's private speech depends on the situation (Behrend et al, 1992;Lee, 1999;Winsler, 1998, Winsler & Diaz, 1995. Thus, similar to what has been found concerning the usefulness of maternal reports for studying other, rather specific and curious child behaviours, such as the presence of imaginary companions and personified objects (Gleason, 2004), it would appear that maternal reports may provide useful information about children's private speech as well. Parents were also practically uniformly positive in their attitudes about private speech use in their children.…”
Section: Discussionsupporting
confidence: 57%
“…The common characteristics in both types are that ICs are named and converse and interact with a child for several months. The prevalence of ICs varies across studies, depending on the definition of IC, children's age and country, but research suggests that nearly half of all children have the experience of engaging with an IC (Gleason, 2004;Singer & Singer, 1990;Taylor, 1999). An important research question is how children create an IC.…”
Section: Parental Behaviour and Children's Creation Of Imaginary Compmentioning
confidence: 97%
“…Future laboratory studies should be particularly affected by some of the independent investigations in which researchers have critically examined current techniques (Ball, 2003;Gleason, 2004a;Klausen & Passman, 2004). The results of two of those studies have demonstrated that a primary tool in research on pretend companions-the use of retrospective reports-may be unreliable.…”
Section: Emergence Of the Fieldmentioning
confidence: 99%
“…Although online research may raise some validity issues, it may provide a valuable tool for future research on pretend companions because bringing parents, their children, and the pretend companions to a laboratory can be difficult. Gleason (2004a) advanced the issue of report accuracy even further by examining concurrent rather than retrospective reports in comparing children's descriptions of their pretend companions with their parents' descriptions. Gleason (2004a) found high contemporaneous parent-child agreement regarding general information about the child's pretend companions (e.g., number of pretend companions) but more disagreement regarding specific details (e.g., their ages).…”
Section: Emergence Of the Fieldmentioning
confidence: 99%